PERBEDAAN EFEKTIVITAS INTERVENSI INFRARED DAN PLANTAR FASCIA STRETCH DENGAN INTERVENSI INFRARED DAN CALF RAISES TERHADAP PENURUNAN NYERI PLANTARIS PADA KARYAWAN PEREMPUAN DI RAMAYANA BALI MALL DENGAN SEPATU HAK TINGGI - Ni Nyoman Devi Yani Prabashanti; Ni Luh Nopi Andayani; I Wayan Gede Sutadarma (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
ABSTRACT The aim of this research is to understand the differences between the effectiveness of infrared intervention and plantar fascia stretch and infrared intervention and calf raises toward reduction of plantar heel pain. This research is an experimental research with pre test and post text two groups design. The sample of this research is 30 people which are divided into two groups. This result indicates that there is a reduction of pain in each group. In difference test between first and second group by using independent sample t-test the result is p=0.847 (p> 0.05 ). Based on the result, it can be concluded that infrared intervention and plantar fascia stretch is as good as infrared intervention and calf raises toward reduction of plantaris pain. Keywords: Plantar heel pain, plantar fascia stretch, calf raises, infrared, VAS.